1976
DOI: 10.1210/jcem-43-5-1094
|View full text |Cite
|
Sign up to set email alerts
|

Visual Failure During Replacement Therapy in Primary Hypothyroidism with Pituitary Enlargement

Abstract: A 34-year-old woman with longstanding untreated thyroprivic hypothyroidism and pituitary enlargement is reported here in whom visual failure coincided with thyroid hormone replacement. Visual fields were normal after 30 years untreated hypothyroidism, but severe concentric field constriction developed during the first 6 months of therapy and was relieved by hypophysectomy. Plasma TSH and prolactin remained elevated during 10 months replacement therapy, but both were suppressed by preoperative hyperreplacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A systematic autopsy study of 64 patients with primary hypothyroidism (256) showed diffuse and nodular thyrotroph hyperplasia in, respectively, 69% and 25% of cases; in 12%, an entity called "tumorlet formation" (incomplete monomorphism, lack of destruction of reticulin network) " was described as an intermediate stage between nodular hyperplasia and adenoma; true adenomas were present in 12 + patients (older on average), with five of them staining for TSH. In reviewing the literature, we found other pathological reports, including autopsies (257)(258)(259)(260)(261)(262) and surgical cases A (263)(264)(265)(266)(267)(268)(269). Since the 1950s, much progress has been made in defining the different types of pituitary cells, with the in-A troduction of electron microscopy, specific staining (for thyrotrophs: alcian blue, aldehyde-thionin), and immunostaining (immunoperoxidase).…”
Section: Anatomic Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic autopsy study of 64 patients with primary hypothyroidism (256) showed diffuse and nodular thyrotroph hyperplasia in, respectively, 69% and 25% of cases; in 12%, an entity called "tumorlet formation" (incomplete monomorphism, lack of destruction of reticulin network) " was described as an intermediate stage between nodular hyperplasia and adenoma; true adenomas were present in 12 + patients (older on average), with five of them staining for TSH. In reviewing the literature, we found other pathological reports, including autopsies (257)(258)(259)(260)(261)(262) and surgical cases A (263)(264)(265)(266)(267)(268)(269). Since the 1950s, much progress has been made in defining the different types of pituitary cells, with the in-A troduction of electron microscopy, specific staining (for thyrotrophs: alcian blue, aldehyde-thionin), and immunostaining (immunoperoxidase).…”
Section: Anatomic Pathologymentioning
confidence: 99%
“…Since the review article written by one of us (158), the reports have been enriched by better imaging and hormonal studies, including dynamic tests. For this article, we reviewed 210 published cases (83% females, 76% adults), very uneven in the depth of the analysis and the focus, depending on the year of publication and the specialty of the authors (257,259,260,(263)(264)(265)(266)(267)(268)(269).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the cases described by Melnyk & Greer (1965) and Herlant et al (1966), the presenting clinical syn¬ drome was that of hypothyroidism associated with menstrual disturbances, galactorrhoea and eleva¬ tion of serum Prl, which are not uncommon in primary hypothyroidism (Honbo et al 1980). Nor¬ malization of serum Prl and cessation of galactor¬ rhoea are known to occur with adequate replace¬ ment of thyroid homrone sometimes taking as long as 1 year (Stockigt et al 1976). Moderate elevations of serum Prl with persistence of amenorrhoea and galactorrhoea, after 1 year of thyroid replacement, in our patient, suggested before surgery a primary pituitary involvement, i.e., a Prl-secreting ade¬ noma.…”
Section: Discussionmentioning
confidence: 88%
“…We SINCE the first report of pituitary hyperplasia due to primary hypothyroidism by Niepce in 1851 [1], the disorder has been well described [2][3][4][5][6][7][8] . However, despite recent progress in imaging techniques, it is very difficult to distinguish between hyperplasia and TSH-producing adenoma of the pituitary, even when high-resolution contrast-enhanced computed tomography (CT) or gadolinium (Gd)-enhanced magnetic resonance imaging (MRI) was used [9].…”
Section: Introductionmentioning
confidence: 99%